Nutritional anaemia: clinical and haematological presentation in children - Vaidya, Sunil S.; Nakate, Dayanand P.; Gaikwad, Shahaji Y.; Patil, Ramesh S.; Ghogare, Manoj S. (International Journal of Contemporary Pediatrics, 2019)
Background: There are three main causes of anemia, decreased production of RBCs, and excessive destruction of RBCs or Excessive blood loss. In India, the main reason of anaemia is the decreased production due to nutritional deficiency. The main nutrients required in the process of haemoglobin production are iron, folic acid and cyanocobalamine. The objective of the present study was to find the clinical presentations and hematological changes in children with nutritional anaemia. Methods: This Cross-sectional study was conducted from January 2018 to October 2018 in the department of Paediatrics of Ashwini Rural Medical College Hospital and Research Centre, Solapur. Children visiting the paediatric OPD due to any illness and having clinical suspicion of anemia were initially screened for inclusion in the study. Detailed laboratory investigation such as CBC, peripheral blood for Leishman’s stain and reticulocyte count were performed. Serum Ferritin, vitamin B12, folic acid levels were also done to ascertain the cause of anemia. World Health Organization recommended criteria were used to diagnose and grade the anemia. Results: A total of 405 anemic children were included in the study. Out of that 213 were boys and 192 were girls. A total of 226 children presented with mild anemia. The most common clinical presentation was respiratory tract infection, found in 62.22 % of children followed by fever in 53.09 % of children. Maximum numbers of patients were suffering from iron deficiency anemia, followed by folic acid deficiency. Deficiency of both of these nutrients was also common. Vit B12 deficiency was found in only 5 children. Conclusions: The study concluded that iron deficiency anemia was the commonest nutritional anemia in children in the age group of 5 to 15 years. Second most common deficiency was of folic acid. Majority of the anemic patients presented with respiratory tract infection and fever.